Ethnobotanical Significance from Bungo Range National Park, Sarawak - Meekiong, Kalu; Freddy, Yeo Kuok San; Teo, S. P.; Liam, J.; Zinnirah, Shabdin; Mohd Effendi, Wasli (Sarawak Museum Department, 2021)
A study was conducted to document traditional knowledge on plants with economic and ethnobotanical significance used by the communities in the vicinity of the boundary of Bungo Range National Park (BRNP). Eight key villages were selected for this study, viz. Tringgus, Pedaun Bawah, Bijuray Mongag, Puruh Semadang, Bengoh Rais, Temurang, Abang Kiding and Rejoi. The surveys encompass interviews, field samplings with documentation and the preliminary results are presented. A total of 366 species from 261 genera and 102 families of plants with ethnobotanical uses were recorded. The family Zingiberaceae (9 genera, 22 species) is most utilised by the communities near the BRNP, followed by Euphorbiaceae (11 genera, 18 species) and Fabaceae with 16 species from 13 genera; whereas Asteraceae and Piperaceae were the two most popular plant families used by the Bidayuh communities for medicinal purposes whilst Zingiberaceae, Anacardiaceae, Cucurbitaceae and Poaceae were the four most popular plant families harvested for foods. More work still remains to be done as this documentation is still far from satisfactory.